Metal‐Bonded Redox‐Active Triarylamines and Their Interactions: Synthesis, Structure, and Redox Properties of Paddle‐Wheel Copper Complexes. Issue 3 (29th January 2019) - Akintola, Oluseun; Böhme, Michael; Rudolph, Manfred; Buchholz, Axel; Görls, Helmar; Plass, Winfried
Abstract: Invited for this month's cover picture is the group of Professor Winfried Plass at the Institute of Inorganic and Analytical Chemistry, Friedrich Schiller University, Jena (Germany). The cover picture shows a scene illustrating the need to investigate the properties of building blocks for complex systems to enable the basic design of new functional materials. The utilized triphenylamine ligands are constituting parts of the currently investigated "Jena University Magnetic Polymer" (JUMP) series. Read the full text of their Full Paper at10.1002/open.201800243 . Abstract : " Both paddle‐wheel units and triarylamine linkers are basic constituents found in several frameworks. Understanding the properties of these building blocks and their interactions facilitates the design of corresponding functional materials.. ." Find out more about the story behind the front cover research at10.1002/open.201800243 .